Effects of weighted vests and sled towing on sprint kinematics - Cronin, J.; Hansen, K.; Kawamori, N.; McNair, P. (Sports Biomechanics, 2008)
In this study, we compared sprint kinematics of sled towing and vest sprinting with the same relative loads. Twenty athletes performed 30-m sprints in three different conditions: (a) un-resisted, (b) sled towing, and (c) vest sprinting. During sled towing and vest sprinting, external loads of 15% and 20% of body mass were used. Sprint times were recorded over 10 and 30 m. Sagittal-plane high-speed video data were recorded at 5, 15, and 25 m from the start. Relative to the un-resisted condition, sprint time increased (7.5 to 19.8%) in both resisted conditions, resulting mainly from decreased step length ( - 5.2 to - 16.5%) with small decreases in step frequency ( - 2.7 to - 6.1%). Sled towing increased stance phase duration (14.7 to 26.0%), trunk angle (12.5 to 71.5%), and knee angle (10.3 to 22.7%), and decreased swing phase duration ( - 4.8 to - 15.2%) relative to the un-resisted condition. Vest sprinting increased stance phase duration (12.8 to 24.5%) and decreased swing phase duration ( - 8.4 to - 14.4%) and trunk angle ( - 1.7 to - 13.0%). There were significant differences between the two resisted conditions in trunk, thigh, and knee angles. We conclude that sled towing and vest sprinting have different effects on some kinematics and hence change the overload experienced by muscle groups.